The Problem of Forming Future Economistʼs Readiness to Foreign Language Professional Communication - Yaroshchuk, Iryna; Blashkiv, Olha (Pedagogical Discourse, 2015)
The article analyses the scientistsʼ approaches to understanding the essence of research key concepts. The main factors of readiness of the future economist to professional foreign language communication have been determined. They are the maturity of functional linguistic personality of the future economist; the maturity of professional abilities and skills of verbal and communicative behavior; the availability of professional and communicative skills, qualities, and knowledge of future specialists in economic sphere. The essences of the concepts «lingual personality of an economist» and «speech behavior of an economist» are grounded. The main factors that affect the mastering of certain algorithms of professional and communicative behavior are determined. It has been defined that the educational process at the economic university is specially organized. It is accompanied by constant reproduction of diverse professional communications. It has been supplemented the professiogram of future economist from the position of business communication. It has been concretized the specifics of economic activity, which involves mastering the communication skills for fulfillment of professional tasks. The main reasons for low level of readiness of the future expert to professionally-communicative activity are determined. The results of the scientific research that confirm the efficiency of the suggested technique are represented. Prospects for further research have been outlined. It exists the necessity to separate the criteria and indicators which can determine the level of readiness of the future economist for the professional foreign language communication.